Olfactory and taste dysfunctions in COVID-19. Issue 3 (June 2021) - Rouadi, Philip W.; Idriss, Samar A.; Bousquet, Jean
Abstract : Purpose of review: Olfactory dysfunction (OD) can be a single and early prominent symptom of severe acute respiratory syndrome (SARS)-COV-2 infection unlike middle east respiratory syndrome (MERS) and SARS. OD data are very informative but many are not peer-reviewed, often inconclusive and may reveal variable and sometimes contradictory results. This is often due to incongruent data of subjective and objective OD testing. Mechanistic pathways of OD and taste dysfunction (TD) are slowly unveiling, not infrequently extrapolated from historical models of SARS and MERS and are still partly unclear. Recent findings: We reviewed the literature on OD and TD during the COVID-19 pandemic analyzing current data on pathogenesis and clinical correlates including prevalence, recovery rates, risk factors, and predictive power. Also, we evaluated various methods of subjective and objective olfactory testing and discussed challenges in management of patients with OD and rhinitis during the pandemic. Summary: Subjective evaluation of smell disturbances during COVID-19 pandemic likely underestimates true prevalence, severity, and recovery rates of OD when compared to objective testing. OD is predictive of COVID-19 infection, more so when associated with TD. Recognizing inherent limitations of both subjective and objective OD and TD testing enables us better to manage chemosensory dysfunction in COVID-19 patients. Besides, current mechanistic data suggest neurotropism of COVID-19 for olfactory neuro-epithelium and a potential role of transient receptor potential (TRP) channels. Future studies are needed to explore further the neurogenic inflammation in COVID-19.